GENDER BASED POLICIES AND THE MYTH OF COMMONALITY IN KENYA - Yamo, Helen (My University, 2011)
The issue of gender as a critical facet of development remains one of utmost importance for many African countries including Kenya. Women‘s role in the economic, social and political development process has formed a major part of the development discourse, notably since the commencement of the UN Decade for Women in 1975. Debates in these areas have evolved over the years to display a more sophisticated understanding of the interplay between gender relations and development. One of the most significant reasons for undertaking this exploratory study on Kenya‘s gendered approach to development is the recognition that, despite the increase in development initiatives and perceived government commitment to engendering national policies, there is still a long way to go in improving the welfare of a majority of women in Kenya. The study attempts to establish in what way, the globalisation of the gender agenda has affected development of gendered policies in Kenya and in turn the overall goal of gender equality as an aspect of social justice and human rights for women. The study analyses the content of existing gendered policies in Kenya, the approaches they employ for achieving women‘s advancement and how by overlooking diversity in women they have adversely affected the efficacy of state efforts towards transforming society and accomplishing women‘s advancement
MM - P&DM
Keywords: Gender policies; Kenya